SEKSUALITAS DALAM LONTAR TINGKAHING SARASMI IMPLIKASI TERHADAP MASYARAKAT DI KECAMATAN DENPASAR TIMUR - Ni Luh Gede Astiti Dewi (Sanjiwani: Jurnal Filsafat, 2019)
Lontar Tingkahing Sarasmi explained about sexual relations at the time of marriage which in it explained sexuality ethics when having sexual relations so that they could reach the peak of sexual pleasure and the ethics of getting the desired son. So knowing this can help the community to deal with problems in the household and get the children they want. Then later children who are born will be a generation that has good quality and can have a good impact on the environment. In Lontar Tingkahing Sarasmai has the concept of sexuality which includes religious concepts and concepts of the use of sexuality. In the concept of sexuality, this explains the love of the gods in the human body so that sexual relations are said to be sacred and there is a prohibition on sexual intercourse because it can affect the character of the child. In addition, there are sexuality ethics, namely: ethics of having sex with wives, ethics of wife holding, ethics of wanting sons and daughters, ethics of wanting powerful sons, ethics of wanting sons and daughters of the main, ethics of wanting beautiful children, and ethics of wanting long-lived sons. As well as how the implications of sexuality in Lontar Tingkahing Sarasmi on the people in East Denpasar Subdistrict, including lifestyle implications, implications for community social behavior, implications for people who apply sexuality ethics in Lontar Tingkahing Sarasmi, and implications for people who do not apply sexuality ethics in Lontar Tingkahing Sarasmi.